(untitled) (CaJoST, 2025)
The study investigated the effect of particle size on mechanical, water absorption, and thermal properties of polyester composites filled with flamboyant seed particles. The composites were made using polyester filled with 10 wt% flamboyant seed of various particle sizes. The results showed that the composites’ bending and impact strengths decreased with particle size, with 100 µm particles having the highest values of 46.99 MPa and 1.86 J/m2, respectively, while the flexural modulus, hardness, and water absorption increased with particle size. The micrographs of fractured samples showed that particles of 100 µm had better interfaces and a homogenous dispersion within the polyester matrix, resulting in improved properties. The thermograph showed that 100 µm particles have better thermal stability with an onset decomposition temperature of 318 oC and maximum weight loss at 373 oC. The composite with a 100 µm particle size showed good mechanical and thermal properties suitable for low-load-bearing applications.